Bioactive composites based on double network approach with tailored mechanical, physico‐chemical, and biological features. Issue 12 (12th September 2018) - D'Amora, Ugo; Ronca, Alfredo; Raucci, Maria Grazia; Lin, Hai; Soriente, Alessandra; Fan, Yujiang; Zhang, Xingdong; Ambrosio, Luigi
Abstract: Hyaluronic acid (HA)‐based hydrogels are one of the most promising naturally derived biomaterials for tissue engineering applications, as they can play an important role in many key cellular processes. In this study, HA was chemically functionalized with photo‐cross‐linkable motifs by reacting with methacrylic anhydride (MA) to obtain methacrylated hyaluronic acid (MeHA). A range of MA/HA molar ratios was used to obtain different degrees of substitution (DS) ranging from 3.5% to 74.5%, as showed by nuclear magnetic resonance and attenuated total reflection spectroscopy. By fine tuning the DS, the chemical reaction parameters, and the polymer concentration, it was demonstrated the possibility to tailor their mechanical features. Double network (DN) hydrogels were prepared through the synergic use of MeHA and polyethylene glycole diacrylate (PEGDA). To improve the biological properties of DN hydrogels, bioactive solid signals such as hydroxyapatite nanoparticles (HAp) prepared by sol–gel approach were used in combination with DN hydrogels to obtain an advanced composite material with dual function in terms of mechanical and biological support for soft/hard tissue formation. The results highlighted that composite‐DN hydrogels showed a 10‐time increase of the storage modulus, if compared to neat MeHA, and an early alkaline phosphatase expression from human mesenchymal stem cells in basal medium. This work can be considered a first systematic approach for the designing of photo‐cross‐linkable hydrogels, based on a combination of natural/synthetic polymers and HAp, that could be applied in three‐dimensional additive manufacturing techniques such as stereolithography. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3079–3089, 2018.